A novel recombinant vaccine candidate comprising PBP2a and autolysin against Methicillin Resistant Staphylococcus aureus confers protection in the experimental mice. (November 2017) - Haghighat, Setareh; Siadat, Seyed Davar; Sorkhabadi, Seyed Mehdi Rezayat; Sepahi, Abbas Akhavan; Mahdavi, Mehdi
Highlights: Immunization with PBP2a/r-autolysin induced specific antibodies with bioactivity in opsonophagocytosis. Immunization with PBP2a/r-autolysin as a candidate vaccine increased the level of immune response in experimental challenge. Immunization with PBP2a/r-autolysin decreased bacterial load in kidney. Immunization with mixture of PBP2a/r-autolysin fully protected experimental mice in the bacterial challenge. Abstract: The methicillin-resistant Staphylococcus aureus infection is a hot topic area in microbiology research. Here a novel vaccine candidate consisting of recombinant PBP2a and autolysin proteins were used. The proteins over expressed in E.coli BL21 (DE3) cells, and purified by the Ni-NTA affinity column and conjugated using EDAC and ADH as a linker and spacer, respectively. To investigate the immunogenicity and protective effects of recombinant proteins, 5 and 20 μg of proteins in various formulations were subcutaneously injected in different groups. Two booster vaccinations were carried out in three-week intervals and blood samples were collected three weeks after each injection. To evaluate the immune response, total IgG, IgG1, IgG2a, and IgG2b were analyzed. Immunization of mice with r-autolysin and r-autolysin-PBP2a mixture raised total IgGantibody. Additionally, both IgG1 and IgG2a responses induced. Opsonophagocytosis assay showed that anti r-PBP2a and r-autolysin IgG not only promoted phagocytosis of S.aureus, but also decreased the number of viable bacterial cells. Furthermore, survival rate of experimental mice increased in the bacteremia infection. Our results demonstrated that active vaccination with a mixture of r-PBP2a/r-autolysin and conjugate form vaccine reduced the mortality rate and protected mice against lethal MRSA challenge as well as single proteins.